The First Balkan War according to French journal Le Temps” and the Western European stereotypes concerning the Balkan peoples - Sajkowski, Wojciech (Balcanica Posnaniensia. Acta et studia, 2012)
“Le Temps” was one of the most important French newspapers of the first half of XXth century. In the first two months of the first Balkan war the progress of this conflict was the most important subject for the editors of “Le Temps”. The information provided by the daily had a binary character. On the one hand the readers might found the descriptions of diplomatic and military operations of the states participating in conflict, and the other political powers interested in the situation in the region. On the other hand the journal systematically published large commentaries made by the political commentators and the Balkan correspondents of the daily. In the articles published in “Le Temps” one can find the images of Balkans which are typical for Western European image of Balkans, which started to emerge in the beginning of XVIIIth century. It is important to underline that this image of Balkans presented in “Le Temps” did not concern only politics and war. The conflict became a pretext for the presentation of wild Balkan nature and the traditional culture of the Balkans. In the articles published in the newspaper it is possible to find also the reflections concerning the backwardness of social structures of Balkan people and their civilizations, as well as the remarks on the process of modernizations of those societies caused by military mobilization. “Le Temps” promoted the Western European stereotypes about Balkans, which up to that time were present mainly in travel journals, not so influential as the daily journals. The representation of Balkans presented by “Le Temps” was the synthesis of the images already known. The example of this journal shows that the image of Balkan people in the time of the Balkan war may be considered as the climax of the process of evolution of the Balkan stereotypes.